PYRETHROIDS RESISTANCE IN CULEX QUINQUEFASCIATUS (SAY) (DIPTERA: CULICIDAE) POPULATIONS FROM BAUCHI STATE, NIGERIA - Umar Aliyu (FUDMA Journal of Sciences, 2024)
This study examines pyrethroid resistance in Culex quinquefasciatus mosquitoes collected from some selected Local Governments Areas of Bauchi State, North-Eastern Nigeria. Insecticide resistance to different phyrethroids was determined using WHO bioassay method. The mosquitoes were also pre-exposed to Piperonyl butoxide (PBO) using the WHO method as part of the synergist assay. The results obtained from this study indicated that Culex quinquefasciatus showed resistance to deltamethrin in Misau (70% mortality), permethrin resistance was detected in Bauchi (58% mortality) and Katagum (37% mortality). Phyrethroids resistance was not detected in Lamda-cyhalotrin and alphacypermethrin. Pre-exposure to PBO in Bauchi LGA has led to 100% mortality of culex mosquitoes exposed to deltamethrin and lambda-cyhalothrin while mortality to permethrin increased from 58% to 95%. In Misau, Pre- exposure to PBO led to 100% mortality of mosquitoes exposed to permethrin and alphacypermethrin while in deltamethrin exposed mosquitoes, PBO increased the mortality from 70% to 90% mortality. The study revealed high pyrethroids resistance of Cx. quinquefasciatus in Bauchi state which causes serious problems in the management of insecticides resistance and also diseases transmitted by this mosquito.